The Relationship between Prevention Methods and Unwanted Pregnancy - Gilasi, Hamid Reza; Akbari, Hossin; Darvishi, Fatemeh; Kazemi, Zohreh; Gharlipour, Zabihollah; Heidarian, Mahbobeh (Advances in Nursing & Midwifery, 2013)
Abstract Background and Aim: Unwanted pregnancy occurs as a result of failure of prevention methods or lack of such methods. The essential aim of family planning is to prevent women from unwanted pregnancies. This study explores the relationship between unwanted pregnancy and contraceptive methods. Materials and Methods: In this case-control study, 90 women with unwanted pregnancies (cases) and 90 women with wanted pregnancies (control) that referred to health centers in Kashan, central Iran were randomly selected in 2000-2010 and a pregnancy questionnaire was administered. Also, telephone interview were completed. Then, the collected data was analyzed using tests such as chi-square, t-test and fisher exact tests through SPSS software. Results: The mean age of case group women was 30.4±5.9 and in the control group it was 27.4±4.9. Statistically significant relationships were found between education, spouse occupation, age, previous unwanted pregnancy, and unwanted pregnancy (p<0.05). No statistically significant relationship was found between type of pregnancy and the number of abortions and previous unwanted pregnancy, age at marriage, employment, and income. Methods used for contraception in the order of significance included withdrawal (50%), condoms (33.3%), and pills (14.4%), respectively. Statistically significant relationship between the types of a method was not observed. Using the Mantel Haenszel method, statistically significant relationship was found between frequency of using the methods and the total number of children, pregnancies and other similar factors. Conclusion: Since the withdrawal method used by women was the most significant factor in the study, women must be encouraged to use reliable contraceptive methods for preventing unwanted pregnancy. Keywords: unwanted pregnancy, Prevention methods, Family